Differences in Parental Burnout: Influence of Demographic Factors and Personality of Parents and Children - Vigouroux, Sarah Le; Scola, Céline (Frontiers in Psychology, 2018)
Parental burnout is a syndrome related to parenthood and characterized by three dimensions: emotional and physical exhaustion, emotional distancing of parents from their children, and loss of parental accomplishment. Many factors can explain the interindividual differences in parental burnout (Roskam, Raes, & Mikolajczak, 2017). In a study conducted among 372 French parents, we examined the relationship between parental burnout, demographic factors (age of parent and child(ren)), age of parent at first birth, total number of children, and number of children present in the family home) and parent-assessed dispositional factors (personality traits of parent and child(ren)). Results for demographic factors showed that the younger the parents we surveyed, the higher their reported sense of parental accomplishment, although they also tended to feel more exhausted. We observed a similar pattern of results when we looked at the children’s ages. In addition, the number of children at home slightly increased the emotional distance between parent and child(ren). Results for the parents' dispositional factors showed that all three personality traits we investigated, as well as their different facets (lack of emotional control and lack of impulse control for neuroticism, meticulousness and perseverance for conscientiousness, and cooperation and friendliness for agreeableness), were related to parental burnout and its three dimensions. More specifically, parental meticulousness and lack of emotional control were both risk factors for developing parental burnout. By contrast, agreeableness and perseverance were protective factors. With regard to the children, the same three personality traits were linked to the three dimensions of parental burnout. Having children they perceived as having a high level of neuroticism reduced parents’ sense of parental accomplishment and increased their emotional exhaustion and distancing. The opposite relationships were found for agreeableness and conscientiousness. There were no significant relationships between parental assessments of their children’ extraversion and openness and parental burnout and its three dimensions. The parent’s personality explained 42.3% of the variance in parental burnout, and the child(ren)'s personality (parent-assessed) explained 13.8%. Taken together, these results demonstrate the importance of considering the personality of both parents and children in the study of parental burnout.